Effect of Carbon Fiber Addition on the Microstructure and Wear Resistance of Laser Cladding Composite Coatings - Jianfeng Li (Coatings, 2019)
In this study, the effect of carbon fibers (CFs) on the microstructure and wear resistance of Fe-based alloy coating produced by laser cladding was investigated by X-ray diffractometer (XRD), scanning electron microscopy (SEM), energy-dispersive spectrometer (EDS), and wear tester. The results indicated that with the addition of CFs, the microstructure of the composite coating mainly transformed from α-Fe cellular dendrites and γ-Fe/(Cr, Fe)7C3/CrB eutectics to bulk-like (Cr, Fe)7C3, nano-size B4C, and γ-(Fe, Ni)/(Cr, Fe)23C6 lamellar eutectics. Additionally, the microhardness and wear resistance of the composite coating compared with the original coating both increased by approximately two times. The original coating showed the dominant wear mechanisms of micro-cutting and serious brittle spalling, while the composite coating with CFs showed the main wear mechanism of slight scratching.